Identification of block-oriented nonlinear systems based on input-output data - Li, Guoqi (2012)
This thesis deals with the identification of block-oriented nonlinear systems. Block-oriented nonlinear systems are composed of linear time-invariant dynamic systems and nonlinear static functions, which are interconnected in different ways. Hammerstein systems, Wiener systems and Hammerstein-Wiener systems as well as Wiener-Hammerstein systems are some well-known examples of block-oriented systems. The main achievements are in the development of new models and new algorithms in identifying block-oriented nonlinear systems.